Female-to-Male Transmasculine Adult Health: A Mixed-Methods Community-Based Needs Assessment. (September 2013) - Reisner, Sari L.; Gamarel, Kristi E.; Dunham, Emilia; Hopwood, Ruben; Hwahng, Sel
BACKGROUND: There is a dearth of health research about transgender people.OBJECTIVES: This mixed-methods study sought to formatively investigate the health and perceived health needs of female-to-male transmasculine adults.DESIGN: A cross-sectional quantitative needs assessment ( n = 73) and qualitative open-ended input ( n = 19) were conducted in June 2011. A latent class analysis modeled six binary health indicators (depression, alcohol use, current smoking, asthma, physical inactivity, overweight status) to identify clusters of presenting health issues.RESULTS: Four clusters of health indicators emerged: (a) depression; (b) syndemic (all indicators); (c) alcohol use, overweight status; and (d) smoking, physical inactivity, overweight status. Transphobic discrimination in health care and avoiding care were each associated with membership in the syndemic class. Qualitative themes included personal health care needs, community needs, and resilience and protective factors.CONCLUSIONS: Findings fill an important gap about the health of transmasculine communities, including the need for public health efforts that holistically address concomitant health concerns.